1960
DOI: 10.1083/jcb.7.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Endoplasmic Reticulum

Abstract: Cells of onion and garlic root tips were examined under the electron and phase contrast microscopes after fixation in KMnO4. Special attention was focused on the distribution and behavior of the endoplasmic reticulum (ER) during the several phases of mitosis.Slender profiles, recognized as sections through thin lamellar units of the ER (most prominent in KMnOa-fixed material), are distributed more or less uniformly in the cytoplasm of interphase cells and show occasional continuity with the nuclear envelope. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

1961
1961
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(75 citation statements)
references
References 36 publications
(37 reference statements)
5
70
0
Order By: Relevance
“…Except for their double nature the spindle lamellae are similar to parts of the E R described by Porter and Machado (13) in plant cells, and these authors, whom I quoted earlier, suggested that this might be the case. The observations show that in Walker tumor cells in anaphase the spindle lamellae come into relation with the surface of the chromosomes and appear to be involved in the formation of the nuclear membrane.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Except for their double nature the spindle lamellae are similar to parts of the E R described by Porter and Machado (13) in plant cells, and these authors, whom I quoted earlier, suggested that this might be the case. The observations show that in Walker tumor cells in anaphase the spindle lamellae come into relation with the surface of the chromosomes and appear to be involved in the formation of the nuclear membrane.…”
Section: Discussionmentioning
confidence: 53%
“…Chentsov (5) has independently and very briefly referred to some equivalent "five-layered" structures in cells of an induced rhabdomyoblastoma. Recently, the finding of the "spindle filaments" in animal cells was briefly reviewed by Porter and Machado (13) who compared the cytoplasmic structures of mitotic animal and plant cells. A component of the spindle in the latter was found to be certain membranes of the endoplasmic reticulum (ER) which were suspended, like drapes, among the other parts of the spindle.…”
Section: Introductionmentioning
confidence: 99%
“…Cell plate formation Porter and Machado (1960) studied the mitosis of onion root tip cells under the electron microscope. They found vesicle-like particles of various sizes ("Phragmosomes") in the equatorial region of dividing cells in telophase.…”
Section: Introductionmentioning
confidence: 99%
“…Neither phragmosomes nor any kind of cytoplasmic elements visible in phragmoplast (Courtesy of Dr. Sato). 4, schematic diagram of phragmoplast and cell plate in onion root tip cell at mid-telophase treated with KMnO4 drawn after the electron micro graph of Porter and Machado (1960). Polysaccharide-micelles and fibrillar texture of phrag moplast destroyed by fixation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation